ORACLES ON FAULTS: A PROBABLE LOCATION OF A “LOST” ORACLE OF APOLLO NEAR OROVIAI (NORTHERN EUBOEA ISLAND, GREECE) VIEWED IN ITS GEOLOGICAL AND GEOMORPHOLOGICAL CONTEXT - Mariolakos, I.; Nikolopoulos, V.; Bantekas, I.; Palyvos, N. (Bulletin of the Geological Society of Greece, 2010)
At a newly discovered archaeological site at Aghios Taxiarches in Northern Euboea, two votive inscribed stelae were found in 2001 together with hellenistic pottery next to ancient wall ruins on a steep and high rocky slope. Based on the inscriptions and the geographical location of the site we propose the hypothesis that this is quite probably the spot where the oracle of “Apollo Selinountios” (mentioned by Strabo) would stand in antiquity. The wall ruins of the site are found on a very steep bedrock escarpment of an active fault zone, next to a hanging valley, a high waterfall and a cave. The geomorphological and geological environment of the site is linked directly to the regional geodynamical context of Central Greece, a region of tectonic turmoil throughout the Pleistocene and Holocene, characterised by distinct landscapes produced by the activity of active fault zones, intense seismicity, and in part, volcanism and hydrothermal activity. The geomorphological and geological similarities of the Ag. Taxiarches site with those of the oracle at Delphi, seem to provide further support to the hypothesis that the former site can well be that of an ancient oracle, given the recently established connections between the geological environment at Delphi and Apollo’s oracle there. Definitive verification of our hypothesis can only be obtained by further, detailed archaeological study, whereas geological/geomorphological, geochemical, and geochronological studies would be necessary to clarify the connection that the cave lying next to the wall remains may had with the site’s function.